Answer:
(fog)(-3)= 11
Step-by-step explanation:
we have from statement:
f(x) = 7x + 4
g(x) = x + 4
so we have:
(fog)(x)= 7(x+4) + 4
(fog)(-3)= 7(-3+4) + 4
(fog)(-3)= 7(1) + 4
(fog)(-3)= 11
Answer:
15 cm
Step-by-step explanation:
Given that :
Reading at one end, initial reading = 3.5 cm
Reading at the other end, final reading = 18.5 cm
Length of needle :
Final Reading - Initial reading
18.5cm - 3.5cm
= 15cm
Answer:
16/13
Step-by-step explanation:
the error is when it was divided, one of the fractions should be reversed to be multiplied
<u> </u><u>4</u><u> </u><u> </u> ÷ <u> </u><u>1</u><u>3</u><u> </u>
7. 28
<u> </u><u>4</u><u> </u> × <u>2</u><u>8</u><u> </u> ,like this
7. 13
= <u> </u><u>1</u><u>1</u><u>2</u><u> </u> ,divide both by 7
91
= <u> </u><u>1</u><u>6</u><u> </u>
13
42 divided by 7 =6 then u times 5 and 6 together . Then times 2 by 6 together so the answer is 30:12
First, since we must follow PEMDAS, we need to do the operation that is first, which is addition.
-3.9 + 6.01 ← Adding a negative means subtracting, then giving the sign of the bigger number.
So now we solved those and we got this answer: 2.11
Now, we need to subtract and re-write the expression.
2.11 - (-7.423) = 2.11 + 7.423= 9.533
Ok....so now we have our final answer, and we have the choices above.
The only answer that matches ours is the last one.
Final answer: 9.533
Hope I helped ^_^